Exploring The Effect of Memory Strategies On Students’ Grammar Skills: Indonesian Learner Context - Thamrin, Sri Wahyuni; Yustika Abrar, Andi Eritme; Yuliartati, Yuliartati (Fakultas Sastra - Universitas Muslim Indonesia, 2022)
One of the major problems faced by Indonesian young learners when learning English grammar is being difficult to memorize sentence pattern with present tense. Grouping with vertical and horizontal lines were believed as an effective memory strategy to memorize the sentence pattern. Therefore, this study targeted to explore whether or not the use of memory strategy was applicable for students when constructing sentences. The research used quasi-experimental design. Each of the classes consisted of 10 participants chosen through total purposive sampling technique. Statistical technique using SPSS program was applied to confirm the hypotheisis. Based on the test of normality, it was found that the probability value of 0.134 is greater than the significance level of 0.05. This indicated that the data were in a normal distribution. Therefore, test of significance was done through parametric test and it showed that the significance value of 0.025 was equal to the probability level of 0.025, which means that there is no significant difference between experimental and control groups’ ability. In conclusion, the use of vertical and horizontal lines were not more effective in improving the students’ grammar skills than the conventional strategy. However, the strategy can be further developed and applied in teaching students with intermediate level.